The Sound of Syntax: How Sad Music Modulates Language Processing in the Brain - Ikram Senen (Winaya Inspirasi Nusantara Foundation, 2021)
Language and music, although conventionally viewed as separate cognitive domains, exhibit same brain underpinnings and processing methods. Recent studies have commenced investigating the impact of emotional music, especially melancholic compositions, on linguistic cognition; nonetheless, this intersection remains little explored. This study rigorously evaluates empirical evidence about the influence of melancholic music on cerebral language processing, with the objective of consolidating existing knowledge and pinpointing theoretical and methodological deficiencies. The study employs a qualitative critical review methodology, utilizing peer-reviewed literature from cognitive neuroscience, psycholinguistics, and affective science, with an emphasis on research that incorporates neuroimaging, behavioral trials, and electrophysiological metrics. The results indicate that melancholic music activates brain areas associated with emotional regulation and language processing, such as the inferior frontal gyrus, superior temporal gyrus, and limbic structures. Exposure to melancholic music seems to augment semantic depth and emotional resonance in language understanding, while possibly hindering performance in tasks necessitating fast syntactic or phonological processing. The effects are influenced by the type of activity and individual variances, including empathy and musical training. The research enhances the comprehension of the emotional aspects of language processing and underscores the utility of emotionally evocative music in educational and therapeutic settings. It also advocates for more ecologically valid, longitudinal, and multimodal research to further clarify these intricate relationships.